Study of the Transmission and Reflection of Electron Waves through a Bridge System Consisting of Quan-tum Dots Using the Tight-Binding Approximation - AL-Saidi, Shakir (University of Thi-Qar Journal of Science, 2023)
In this study, we treat tunneling similarly to the dispersion problem where the wave incident on the barrier is partly transmitted and partly reflected. The transport potential will be related to conduction using the tight-binding model, the steady-state formula, and the Landauer relationship. The tunnel was processed using a bridge model. We studied the effect of changing the size of the quantum dots that make the bridge on the probability of transmission and reflection, the effect of changing the number of quantum dots on them. The transmission and reflection spectrums were compared as functions of the system’s energy spectrum. We also noticed the effect of the transmission and reflection spectrum on the conductivity of the system. The results that have been reached, and will contribute significantly to the manufacture of nano-devices in the not-too-distant ture.